Pengaruh Supervisi Akademik, Budaya Organisasi dan Motivasi Kerja Terhadap Kompetensi Pedagogik Guru SMP Perkumpulan Strada Cabang Jakarta Utara Timur - Prayitna, Anna Maria Satia; Handoko, Yunus; Rachmawati, Ike Kusdyah (Smart Education, 2024)
The quality of Human Resources is one of the factors that determines the progress of a country. Quality human resources cannot be separated from quality education as well. One important aspect of the world of education is teachers. A teacher's job is not only to teach but also to educate students to become quality people. Therefore, a teacher must have sufficient competence. One of the competencies possessed by a teacher is pedagogical competency. Pedagogical competency is a competency that differentiates the teaching profession from other professions. The differences in characteristics of each student and the curriculum that continues to develop are the main reasons that every teacher is obliged to improve his or her pedagogical competence. With adequate pedagogical competence, it is hoped that the level of success in the learning process can be achieved for all students. This research aims to determine and analyze: 1) the influence of academic supervision on teacher pedagogical competence, 2) the influence of organizational culture on teacher pedagogical competence, 3) the influence of work motivation on teacher pedagogical competence, and 4) the influence of academic supervision, organizational culture and work motivation overall together towards teacher pedagogical competence. This research was conducted at the Perkumpulan Strada Middle School, Cabang Jakarta Utara Timur, which consists of four school units. The sampling method used was the saturated or sesus sampling method where all 51 teachers of the Perkumpulan Strada Middle School, Cabang Jakarta Utara Timur, were used as samples for this research. The results of the study show that the academic supervision variable has a positive and significant effect on the pedagogical competence of teachers at the the Perkumpulan Strada Middle School, Cabang Jakarta Utara Timur, and the organizational culture variable also has a positive and significant effect on the pedagogical competence of teachers at the the Perkumpulan Strada Middle School, Cabang Jakarta Utara Timur. Still, the work motivation variable has no effect on the pedagogical competence of teachers at the the Perkumpulan Strada Middle School, Cabang Jakarta Utara Timur. Academic supervision, organizational culture, and work motivation simultaneously have a positive and significant effect on the pedagogical competence of teachers at the the Perkumpulan Strada Middle School, Cabang Jakarta Utara Timur. Keyword: Academic supervision, Organizational Culture, Work Motivation and Pedagogical Competence